Use of computational modeling to analyze productivity in the face of ergonomic changes: a case study of a workstation in the administrative area of the logistics sector - Grancieri, Luiza Diniz; Melo, Isabela Crisóstomo; Campos, Maysa Mendes; Tinoco, Cynara Mendonça Moreira (Brazilian Journal of Production Engineering, 2024)
Occupational health and safety (OHS) is fundamental to promoting occupational health and increasing efficiency in administrative environments. The aim of this study was to investigate the influence of ergonomic changes on the productivity of workers in the logistics sector of a real estate development company. To do this, we used the PDCA Cycle, Ergolandia software for ergonomic work analysis using the RULA and OCRA Checklist methods and Flexsim software to simulate and compare productivity before and after implementing the ergonomic improvements. The results showed an initial reduction of 9.25% in productivity after the implementation of the ergonomic measures, explained by the time it took to settle into the new process. However, significant improvements were seen in the physical and mental health of the workers, which can have a positive impact on the team’s motivation and commitment. As for the limitations of the work, it can be seen that post-improvement times were collected immediately after ergonomic changes, which is insufficient time for workers to adapt. Future studies could replicate the methodology presented in various administrative positions to compare the effectiveness of ergonomic interventions.